[RETRACTED] Conflict in Private Land: The Role of “Yellow Journalism” in the Turmoil of Batu Ceper, Tangerang 1934 - Muhamad Mulki Mulyadi Noor; Susanto Zuhdi (Diponegoro University, 2020)
RETRACTION NOTICE to the article entitled